1982
DOI: 10.1002/1097-0142(19821001)50:7<1248::aid-cncr2820500705>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results and pharmacokinetics of high-dose cytosine arabinoside (HD ARA-C)

Abstract: Four patients with acute nonlymphoblastic leukemia and one malignant teratoma refractory to conventional chemotherapy were treated with high doses of cytosine arabinoside (HD ARA‐C). They received up to 12 cycles of 1.8 to 3 g/m2 every 12 hours applied by 2‐hour infusions. A total of 55 HD ARA‐C infusions was performed. All leukemic patients responded. A complete clearance of blasts from the bone marrow was observed in two patients following 8–12 cycles of 3 g/m2. However, relapses occurred after three and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…NOAC was less prone to deamination as determined in a phase I study [102]. Doses of 600 mg/m 2 in patients were well tolerated without unexpected side effects and led to long plasma half-lives of up to 16 h (versus a few minutes for free cytarabine) [102,103]. However, to the best of our knowledge, this formulation did not enter clinical phase II.…”
Section: From Preclinical Studies To Clinical Trialsmentioning
confidence: 99%
“…NOAC was less prone to deamination as determined in a phase I study [102]. Doses of 600 mg/m 2 in patients were well tolerated without unexpected side effects and led to long plasma half-lives of up to 16 h (versus a few minutes for free cytarabine) [102,103]. However, to the best of our knowledge, this formulation did not enter clinical phase II.…”
Section: From Preclinical Studies To Clinical Trialsmentioning
confidence: 99%
“…There are several human leukemia cell lines available, and only K562 cell line was selected to mimic the clinical situation, since this cell line was found to have higher baseline levels of M2 expression (data not shown), which is similar to those responders of AML patients treated with GTI-2040 and high-dose Ara-C (14). Ara-C is one of the most effective anticancer agents for the treatment of AML, and its therapeutic effect at low or high doses has been extensively studied (24)(25)(26)(27)(28)(29)(30)(31). It has been reported that the metabolism of Ara-C in vitro was greatly enhanced by RNR inhibitors, such as amidox and trimidox (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…AraC pharmacokinetics could better explain the negative impact of dose reduction in patients with PCNSL. This drug exhibits a dose-related CSF bioavailability [8], with CSF levels of 10%-15% of steady-state plasmatic concen- trations [9], and a significant direct correlation between araC dose and CSF end-dose ara-U levels [10]. In a pharmacokinetic study performed on 19 patients with acute leukemia [10], direct correlations between the dose of araC administered and peak plasma araC levels and CSF concentrations have been shown, with a mean end-dose CSF araC level following 3 g/m 2 of araC of fourfold the mean enddose CSF araC level following 0.75 g/m 2 .…”
Section: Discussionmentioning
confidence: 99%